Workshop Pengenalan Gimkit untuk Asesmen Formatif Mode Game Online - Sonny Rohimat; Solfarina Solfarina; Samsiah Samsiah; Fajar Izza Ramdhani; Raisya Fitri; Nisa Aliyah (Jurnal Nusantara Berbakti, 2023)
Assessment is a process carried out to collect information related to student learning development, analyze and interpret it in deciding learning achievement based on certain criteria and aspects. The use of digital-based learning media can provide a pleasant experience for students in the assessment process, but there are still many teachers who have not used it because of the lack of information to teachers about the use of online learning applications and assessment media, especially those based on online game modes. This workshop aims to socialize Gimkit as a digital platform that can be used for learning assessment. This workshop aims to socialize Gimkit as a digital platform that can be used for learning assessment by presenting two resource persons, namely the Chair of the Untirta Chemistry Education Department and the Chair of the Indonesian Teachers Association (IGI) of Serang City. The first resource person explained the application of information technology in learning assessment, while the second resource person introduced the Gimkit platform and demonstrated and practiced the assessments created by the participants. Based on the results of reflection and evaluation, this workshop activity really helped teachers and students innovate to develop fun assessment activities in the classroom.